Modelling learners' understanding through node-link analysis and scoring - Lajis, Adidah; Abdul Aziz, Normaziah (2010)
Assessment is an important component of learning and it also noted that many examinations make heavily used of short answers. This assessment can be a tedious task. This research work proposed a technique that models the teacher's and learner's knowledge to evaluate short free text answer. It is based on a hybrid approach that combines natural language processing, a node-link as a representation technique and the application of information theory in the measurement of learners' understanding. Pearson correlation and exact-and-adjacent agreement have been used as a measurement instrument. Results show that the proposed technique can be applied for the assessment of learners' understanding in tertiary and school level for computer science and science domain.